Analysis of the synchronization between the 2021–2026 RPJMD of Sleman Regency and the 2021–2026 strategic plan of the Sleman Regency Tourism Office - Hakiki, Muhammad Ihsan; Sekaringsih, Riswanti Budi (Jurnal Kebijakan Ekonomi dan Keuangan, 2026)
Purpose – This study aims to analyze the vertical synchronization between the Sleman Regency Medium-Term Development Plan (RPJMD) and the Sleman Regency Tourism Office's Strategic Plan for 2021–2026, specifically regarding tourism attraction development.Methods – This study employed a descriptive qualitative approach with literature review techniques and textual-normative documentation sourced from the Sleman Regency RPJMD and the Sleman Regency Tourism Office's Strategic Plan for 2021–2026.Findings – The results indicate strong vertical synchronization between the two documents. The RPJMD positions tourism as part of creative and innovative economic development, while the Tourism Office's Strategic Plan translates this more specifically into goals of increasing the tourism sector's contribution to Regional Original Income, targets to increase the competitiveness of the tourism sector, and strategies to optimize regional potential and tourist attractions. Implication – The results of this study can serve as evaluation material to strengthen the continuity of tourism planning between the regional and local levels.Originality – This research contributes to strengthening the study of synchronization of regional tourism development planning policies through an analysis of the integration of planning documents across levels of regional government. AbstrakTujuan – Penelitian ini bertujuan untuk menganalisis sinkronisasi vertikal antara Rencana Pembangunan Jangka Menengah Daerah (RPJMD) Kabupaten Sleman dan Rencana Strategis Dinas Pariwisata Kabupaten Sleman Tahun 2021–2026, khususnya dalam pengembangan daya tarik wisata.Metode – Penelitian ini menggunakan pendekatan kualitatif deskriptif dengan teknik kajian literatur dan dokumentasi secara tekstual-normatif yang bersumber dari RPJMD Kabupaten Sleman dan Renstra Dinas Pariwisata Kabupaten Sleman tahun 2021–2026.Temuan – Hasil penelitian menunjukkan bahwa sinkronisasi vertikal antara kedua dokumen tergolong kuat. RPJMD menempatkan pariwisata sebagai bagian dari pembangunan ekonomi kreatif dan inovatif, sedangkan Renstra Dinas Pariwisata menerjemahkannya secara lebih spesifik ke dalam tujuan peningkatan kontribusi sektor pariwisata terhadap Pendapatan Asli Daerah, sasaran peningkatan daya saing sektor pariwisata, serta strategi optimalisasi potensi daerah dan daya tarik wisata.Implikasi – Hasil penelitian ini dapat menjadi bahan evaluasi untuk memperkuat kesinambungan perencanaan pariwisata antara tingkat daerah dan perangkat daerah.Orisinalitas – Penelitian ini berkontribusi pada penguatan kajian sinkronisasi kebijakan perencanaan pembangunan pariwisata daerah melalui analisis keterpaduan dokumen perencanaan lintas level pemerintahan daerah.